Javno-zasebno partnerstvo v teoriji - Vrhnjak, Blaž (Zdravniški vestnik, 2007)
Background In political and other debates much of attention is paid to public - private partnerships (PPPs). These partnerships are perceived as a tool of meeting public demand by private supply. In theory there are at least four different forms of contract partnerships according to the amount of risks transferred to the private sector. Conclusions Public - private partnerships are neither the only neither the preferred way of providing public service. Onone hand they tend to lower financial burden of the public sector but on theother hand PPPs require complex ways of management and monitoring. It is highly important to consider specific circumstances of individual projects in question.
Keywords: health care; Health Policy; Health Services; javni zavodi; Javno zdravstvo; javno-zasebno partnerstvo; organizacija; organization; Organization And Administration; Private Practice; Public Health; Zasebna praksa; Zdravstvena politika; Zdravstvene službe; zdravstvo